SDGs IN ENGINEERING AND TECHNOLOGY:A QUICK GUIDE FOR EDUCATORS - Chee-Ming Chan; Alina Shamsuddin; Azeanita Suratkon (Penerbit UTHM, 2026)
Sustainable development is the responsibility of all, especially for the present generation who would be keeping Earth ‘battered but intact and adequate’ for the future inheritors. This is befitting the definition of sustainable development itself, which is a development that meets the needs of the present without compromising the ability of future generations to meet their own needs. Nonetheless, actions would be unholistic, incomplete or misguided without knowledge. Hence it is important that everyone is aware of the fact that every façade of life on Earth is related to sustainability and our continued existence. This is clearly encapsulated in the 17 Sustainable Development Goals (SDGs) introduced in year 2015. Education, is the key here. This is a concise book written as a quick read by teachers, students or anyone at all who wants to know about SDGs and how each Goal is closely related to the engineering and technology advancement of today. Teachers will find the final chapter on incorporation of the concept in everyday learning of students a quick reference, with simple case studies, examples, tips and tricks to impart knowledge and understanding. If it does not inspire, let it be at least informative, and a nudge to grow the ‘sustainable minds’ of the young.